A rabbit model for evaluating ocular damage from acrolein toxicity in vivo. Issue 1 (16th October 2020) - Gupta, Suneel; Fink, Michael K.; Martin, Lynn M.; Sinha, Prashant R.; Rodier, Jason T.; Sinha, Nishant R.; Hesemann, Nathan P.; Chaurasia, Shyam S.; Mohan, Rajiv R.
Abstract: Acrolein is a highly reactive and volatile unsaturated aldehyde commonly used for producing scores of commercial products. It has been recognized as a chemical weapon since its use during World War I, and more recently, in Syria. Acrolein exposure causes severe eye, skin, and lung damage in addition to many casualties. In the eye, it causes severe pain, eyelid swelling, corneal burns, and vision impairment. Very little information is available about how acrolein damages the cornea and causes vision loss. At present, the lack of clinically relevant animal models limits evaluation of acrolein toxicity and mechanisms specific to the eye. We aim to standardize the mode of delivery and exposure duration of acrolein, damaging the rabbit eye in vivo as an ocular injury model for studying the toxicity of acrolein and developing medical countermeasures. Rabbit eyes were exposed to two modes of delivery (topical and vapor) for different durations (1–5 minutes). Clinical ophthalmic examinations with a slit lamp, stereomicroscope, fluorescein dye, pachymeter, tonometer, and tearing examinations in live rabbits were performed at various times up to 4 weeks. Corneas were histologically diagnosed for transparency, fibrosis, collagens, and neovascularization. Our study successfully established an in vivo rabbit model for evaluating acrolein toxicity to the eye, accounting for different modes and durations of exposure. Abstract : Acrolein is a highly reactive aldehyde that has been used as a chemical weapon. Acrolein exposure causes severe eye damage. The lack of clinically relevant animal models limits evaluation of acrolein toxicity and mechanisms specific to the eye. We aim to standardize the mode of delivery and exposure duration of acrolein, damaging the rabbit eye in vivo as an ocular injury model for studying the toxicity of acrolein and developing medical countermeasures.